Rancang Bangun Sistem Informasi Manajemen Kost Menggunakan Metode Waterfall Berbasis Web - Rizky Azhari Putra; Apriade Voutama (TIN: Terapan Informatika Nusantara, 2026)
This study aims to design a web-based boarding house management and booking information system using the Waterfall method to improve the efficiency of promotion, room search, booking records, and payment monitoring processes that were previously conducted manually. This study employed a software engineering approach, with data collected through observation, document review, and interviews with two students as prospective users. The Waterfall method was applied through requirement analysis, system design, process modeling, and interface prototype development. System modeling focused on Unified Modeling Language, including use case diagrams, activity diagrams, and class diagrams. The results show that the proposed system design produced 18 functional requirements and 11 nonfunctional requirements, with three main actors namely tenants, boarding house owners, and administrators. The core features include location-based boarding house search, room facility details, online booking, payment confirmation, tenant reviews, wishlist, and a boarding house data management dashboard for owners. The system design also produced interface prototypes for guests, tenants, administrators, and boarding house owners. These findings indicate that the proposed system can provide a foundation for developing a more efficient, transparent, and user-oriented boarding house application.